Religious Figures as Unifiers of Moderation in Multicultural Societies - Khairani Soraya (Young Journal of Social Sciences and Humanities, 2025)
This study aims to describe the role of religious leaders in building tolerance in a society that has religious diversity. This paper uses a literature study method by analyzing social media using content analysis. The findings show that religious lectures, interfaith dialogue, and social activities led by religious leaders have a significant contribution in encouraging harmonious relations and mutual understanding between religious groups. In addition, religious leaders have proven to play a role in reducing negative stereotypes and mediating conflicts based on religious differences. This study concludes that the existence of religious leaders as a driver of tolerance values is a key element in maintaining harmony in a pluralistic society.